Case Report of HIV and Neurosyphilis Coinfection in a Recent Migrant: Old Diseases in New Faces - Alexa Van Besien; Ian Paolo Mauricio; Ronald Belfort; Joseph Lykins (Clinical Practice and Cases in Emergency Medicine)
Introduction: Coinfection with human immunodeficiency virus (HIV) and Treponema pallidum represents a unique challenge in management, with increased risk of neurological complications. Haiti is well-known for being disproportionately impacted by the HIV epidemic, with rates of infection ~6 times higher than in the United States (US). Rates of coinfection in Haiti are incompletely characterized but likely high. The US has seen a marked increase in migration from Haiti, with implications for public health and migrant health management. Case Report: A 69-year-old male, recent Haitian migrant presented for subacute altered mental status and visual and auditory hallucinations for approximately four weeks. The patient’s neurological exam was non-focal, but laboratory evaluation showed an elevated paraprotein gap (6.7 grams per deciliter). This prompted concern for infectious etiology. The patient was diagnosed with HIV/AIDS with a CD4+ count of 154 cells per cubic millimeter and a positive rapid plasma reagin test (titer 1:128), with cerebrospinal fluid demonstrating elevated white blood cell count and protein concentration, consistent with neurosyphilis. The patient completed 14 days of intravenous benzathine penicillin G, with hospitalization complicated by hyponatremia and vomiting, which resolved after antibiotics. Conclusion: This case highlights the risk of coinfection with HIV and neurosyphilis in the Haitian migrant population and suggests possible benefit in routine screening for HIV and syphilis in the emergency department, particularly for at-risk populations. Neurosyphilis can be difficult to diagnose, requiring a high index of suspicion. Migrant patients can have difficulty accessing healthcare services, and the emergency department may have a role in screening and initiation of treatment in this population.